Delivery of First Aid to Victims in Road Transportation Accidents - A. V. Baranov (Неотложная медицинская помощь)
Relevance. Most of the victims of road accidents die prior to the arrival of medical staff, therefore, providing first aid to injured people in the first minutes after receiving injuries is very important for saving human life and health. Timely and skillful provision of first aid to victims of road accidents prevents further deterioration of the state of the human body and can positively affect the entire process of its further treatment and rehabilitation.Aim of study. To characterize the delivery of first aid to victims of road traffic accidents at the present stage and to outline possible ways for its improvement.Material and methods. To achieve this goal, an analysis was made of the results of domestic and foreign scientific research and regulatory legal acts on the issue of providing first aid to victims of road accidents. The literature search was carried out in specialized scientific search engines eLibrary, PubMed, Scopus using the keywords: first aid, prehospital stage, road traffic injuries, road traffic accidents. For the analysis, scientific articles published between 1980 and 2020 were selected. Resources with outdated or inaccurate information were excluded, some scientific papers were found by links to articles. The state of the problem of providing first aid to victims of road traffic injuries, for the most part, reflects scientific publications over the past ten years.